ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI PENYAJIAN DATA DI KELAS VII MTs ISLAMIYAH MEDAN T.P 2017/2018 Oleh: - Nursyahbany Sitorus Pane Sitorus Pane; Indra Jaya; Mara Samin Lubis (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
The ability of students' mathematical communication is an aspect that needs to be developed in the learning of mathematics. The purpose of this study is to obtain a description of the mathematical communication ability of class VII students in learning mathematics. This research is a qualitative research. The subject of this research is 6 students of class VII-AMTs Islamiyah Medan who come from high-ability students, medium-skilled students, and low-ability students. Data collection techniques used are observation, interview, and documentation. To know how far students' mathematical communication ability is measured based on indicator of mathematical communication ability ie (1) Ability to express mathematical ideas through oral, written, and demonstrate and visualize it; (2) The ability to understand, interpret, and evaluate mathematical ideas in writing, as well as in other visual forms; (3) The ability to use terms, mathematical notations and structures to present ideas, describe relationships with situational models. The results showed (1) subjects with high ability to have good enough mathematical communication ability on each indicator both indicator 1, 2 and 3; (2) medium-sized subjects also have good mathematical communication skills in indicators 1 and 2 and less well in indicator 3; (3) low-ability subjects have poor mathematical communication skills on each indicator.